Impact of toll-like receptor 4 on the severity of acute pancreatitis and pancreatitis-associated lung injury in mice. Issue 6 (6th February 2009) - Sharif, R; Dawra, R; Wasiluk, K; Phillips, P; Dudeja, V; Kurt-Jones, E; Finberg, R; Saluja, A
Abstract : Background and Aims: Acute pancreatitis is an inflammatory disease involving acinar cell injury, and the rapid production and release of inflammatory cytokines, which play a dominant role in local pancreatic inflammation and systemic complications. Toll-like receptor 4 (TLR4) initiates a complex signalling pathway when it interacts with lipopolysaccharide (LPS), which ultimately results in a proinflammatory response. We hypothesised that TLR4 is important in the pathophysiology of acute pancreatitis, independently of LPS. Using two different models of acute pancreatitis, we investigated how genetic deletion of TLR4 or its co-receptor CD14 effects its progression and severity. Methods: We induced acute pancreatitis by administering either caerulein or l -arginine to wild-type, TLR4 −/−, and CD14 −/− mice. Control mice received normal saline injections. The severity of acute pancreatitis was determined by measuring serum amylase activity, quantifying myeloperoxidase (MPO) activity in the pancreatic tissue, and histologically assessing acinar cell injury. Results: It was found that administering caerulein and l -arginine to wild-type mice resulted in acute pancreatitis (as assessed by hyperamylasaemia, oedema, increased pancreatic MPO activity, and pancreatic necrosis) and associated lung injury. The same treatment to TLR4 −/− or CD14 −/− mice resulted in significantly less severe acute pancreatitis, and reduced lung injury. We found no evidence of either bacteria or LPS in the blood or in pancreatic tissue. Conclusions: The severity of acute pancreatitis is ameliorated in mice that lack either TLR4 or CD14 receptors. Furthermore, these results indicate that TLR4 plays a significant pro-inflammatory role independently of LPS in the progression of acute pancreatitis.